Subjective age and verbal fluency among middle aged and older adults: A meta-analysis of five cohorts. (November 2021) - Stephan, Yannick; Sutin, Angelina R.; Luchetti, Martina; Aschwanden, Damaris; Terracciano, Antonio
Highlights: Subjective age is related to verbal fluency in five samples and a meta-analysis. An older subjective age is related to lower verbal fluency. This association is independent of chronological age, sex, and education. Abstract: Objectives: This study aimed to examine the relation between subjective age and verbal fluency in five large samples of older adults to advance knowledge on the role of subjective age in a complex cognitive function that is an intermediate marker of cognitive impairment and dementia risk. Methods: Participants ( N > 27, 000), aged 32 to 99 years old, predominantly white, were from the Wisconsin Longitudinal Study Graduate (WLSG) and Siblings (WLSS) samples, the Health and Retirement Study (HRS), the Midlife in the United States Study (MIDUS), and the English Longitudinal Study of Ageing (ELSA). They provided complete data on subjective age, demographic factors and verbal fluency. Estimates from each sample were combined in a meta-analysis. Results: Across each of the five samples and in the meta-analysis, an older subjective age was related to lower performance on the verbal fluency task. This association was independent of chronological age and was not moderated by age, sex, nor education. The difference in fluency between individuals with an older and younger subjective age ranged from d  = 0.09 to d  = 0.37 across the five samples. Conclusions: This study found replicable evidence for an association between an older subjective age and lower verbal fluency, extending knowledge about an intermediate marker of cognitive function.